An Analysis of Indefinite Pronouns Proficiency in English Sentences Among Seventh Grade Students at Madrasah Tsanawiah Yayasan Pendidikan Karya Setia (MTS YPKS) Padangsidimpuan - Sari, Siti Meutia; Nasution, Rina Efendi; Meidipa, Lisa Fitri (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2023)
This study aims to analyze the proficiency of seventh-grade students in using indefinite pronouns and identify the challenges they face in mastering this grammatical component. To achieve this, the research adopts a qualitative methodology with random sampling of 58 students. Data were collected through a combination of tests and interviews. The tests consisted of 10 multiple-choice questions and 10 essay questions, designed to assess the students' understanding and application of indefinite pronouns. Following the tests, interviews were conducted with 10 students to gain deeper insights into the reasons behind their difficulties. The results reveal significant challenges among the students in mastering indefinite pronouns. Specifically, 18.96% of students struggled with subject indefinite pronouns, 48.27% with object indefinite pronouns, and 50% with adjective indefinite pronouns. The difficulties were attributed to both internal factors, such as lack of motivation and low language proficiency, and external factors, including ineffective teaching methods and insufficient practice opportunities. The study concludes that the students' mastery of indefinite pronouns is significantly influenced by these internal and external factors. The findings suggest a need for enhanced teaching strategies and targeted interventions to improve students' grammatical skills and overall proficiency in English.